STATE RESPONSIBILITY TOWARDS LAND MAFIA VICTIMS FROM THE PERSPECTIVE OF LEGAL CERTAINTY AND JUSTICE - Gloria Gita Putri Ginting; Ayu Kurnia Sari (RADJA PUBLIKA, 2025)
This study aims to analyze the state's responsibility towards victims of land mafia from the perspective of legal certainty and justice. Land mafia causes serious harm by seizing land rights, weakening legal protection, and reducing public trust in the state. This study uses a normative juridical method with a statutory and conceptual approach. Data were obtained through a literature review of primary, secondary, and tertiary legal materials, then analyzed qualitatively. The results show that the state has a responsibility to prevent, prosecute, and restore the rights of land mafia victims through a transparent land administration system, firm law enforcement, and a fair redress mechanism. Legal certainty has not been fully achieved due to weaknesses in land data validation, official oversight, and slow dispute resolution. From a justice perspective, victims must not only obtain legal recognition but also receive rights restoration, protection from criminalization, and adequate compensation if the state is proven negligent. Therefore, the state's responsibility must be actively realized through improving land governance, strengthening inter-institutional coordination, and providing easy access to justice for victims. This research confirms that protecting land mafia victims is an important part of a state based on law that guarantees legal certainty and justice.